The Circular Attack in Terms of Cognitive Speed, Creativity Awareness for Fencing Students - Abid, Dr. Haitham Hussein (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to recognize the relation among the circular attack in terms of cognitive speed, creativity awareness of students in fencing. The study will also focus on Devising a predictive equation to predict the circular attack in terms of cognitive speed and creativity awareness for students. The experimental program consisted of 100 fencing students from Anbar University College of Sport and Physical Education Sciences. The researchers used the descriptive approach using the method of standard studies, and the method of relational relationships to achieve the goals of the research through the use of the measure of creativity awareness prepared by Enas Muhammad Mahdi al-Mahdawi (2010), which consists in its final form of (28) items, and the cognitive speed test prepared by Aseel Abdul Hamid Abdul Jabar (2010), which consists in its final form of (29) items, to measure cognitive speed. The researchers used the SPSS program to analyze the research data. The researchers found that there is a direct correlation between the performance of the circular attack from a side and the cognitive speed and creativity awareness on the other side. Thus, there is a good possibility to predict the circular attack accuracy based on the cognitive speed and the creativity awareness of the sample.